Evaluation of antibody response to an adjuvanted hapten-protein vaccine as a potential inhibitor of sexual maturation for farmed Atlantic salmon. Issue 71 (December 2017) - Mora, Darcy S.O.; Salman, Mo D.; Myrick, Christopher A.; Rhyan, Jack C.; Miller, Lowell A.; Sætre, Ellen Marie; Eckery, Douglas C.
Abstract: An experimental contraceptive vaccine was evaluated in Atlantic salmon ( Salmo salar ). A peptide derived from the beta subunit of luteinizing hormone (LH) was conjugated to two different carrier proteins, bovine serum albumin (BSA) and keyhole limpet hemocyanin (KLH), and formulated with one of four immunostimulants in a water-in-oil emulsion. Specific antibody responses to the peptide and each carrier protein were evaluated. While the antibody response to KLH was stronger than the response to BSA, both carrier proteins stimulated comparable antibody responses to the LH peptide. The immunostimulant proved to be more important for enhancing the LH peptide antibody response than the carrier protein selection; vaccines containing a combination of Aeromonas salmonicida and Vibrio anguillarum stimulated significantly greater LH peptide antibody production than any of the other three immunostimulants evaluated at 12 weeks post-vaccination. This study provides proof-of-concept for specific antibody production against a hapten-carrier protein antigen in Atlantic salmon and reinforces the importance of vaccine immunostimulant selection. Highlights: Salmon were immunized with a peptide-carrier protein conjugate and immunostimulant. Carrier proteins BSA and KLH stimulated equal levels of anti-hapten antibodies. Antibody production was higher at 12 weeks post-vaccination compared to 8 weeks. A . salmonicida  +  L . anguillarum 'immunostimulant' enhances antibody production.